1976
DOI: 10.1111/j.1365-2621.1976.tb14412.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on Cooking of Rice

Abstract: The mechanism of cooking rice was investigated in this study. The rheological method using the parallel plate plastometer was adopted for measurement of the degree of cooking. The range of temperatures measured ran from 75-150°C. Experimental results showed that cooking rate followed the equation of a first order chemical reaction. We designated the proportional constant as the cooking rate constant, but the slope of Arrhenius plots of the cooking rate constants changed around 110°C. The activation energy of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 2 publications
8
57
2
Order By: Relevance
“…Since it was a slender grain (b = 1.64 mm), the water diffusivity could have been faster than Swarna (b = 1.71 mm) and ADT37 (b = 1.96 mm) variety for the same degree of milling. This confirms to earlier results reported by Suzuki, Kubota, Omichi, and Hosaka (1976). The coarser grain variety ADT37, took the highest optimum cooking time (for complete disappearance of white core) as compared to Pusa Basmati and Swarna.…”
Section: Cooking Qualitysupporting
confidence: 91%
“…Since it was a slender grain (b = 1.64 mm), the water diffusivity could have been faster than Swarna (b = 1.71 mm) and ADT37 (b = 1.96 mm) variety for the same degree of milling. This confirms to earlier results reported by Suzuki, Kubota, Omichi, and Hosaka (1976). The coarser grain variety ADT37, took the highest optimum cooking time (for complete disappearance of white core) as compared to Pusa Basmati and Swarna.…”
Section: Cooking Qualitysupporting
confidence: 91%
“…The cooking rate is the amount of cooked rice as a function of cooking time, and is strongly 254 affected by the temperature and the amount of cooking water (Bello, Tolaba & Suarez, 2007; 255 Suzuki et al, 1976). When water temperature is increased to the gelatinisation temperature, starch 256 granules swell irreversibly, lose their crystallinity and gelatinise (Metcalf & Lund, 1985).…”
Section: Cooking In Excess Water 221 242mentioning
confidence: 99%
“…When a long grain variety was 259 soaked/cooked from 25 -90 °C, the water absorption curves showed a rapid increase in the 260 diffusion of water at around 65 °C (Bello et al, 2007). The changes in the activation energy for 261 diffusion and physical change at 60 °C indicate that below this temperature the structural change of 262 water and rice components was the limiting factor while above 60 °C the diffusion of water became 263 the limiting factor for water absorption with the gelatinised starch physically preventing penetration 264 of water (Bello et al, 2007;Suzuki et al, 1976). These results are consistent with the study of 265 Chakkaravarthi et al (2008).…”
Section: Cooking In Excess Water 221 242mentioning
confidence: 99%
“…The cooking of rice is associated with complete gelatinization of the starch, complex formation, transformation and interactions involving biopolymer by heat treatment in the presence of water. Suzuki, Kubota, Omichi, and Hosaka (1976) reported that cooking rate followed the equation of a first-order chemical reaction.…”
Section: Introductionmentioning
confidence: 99%